Pengaruh Cemaran Mikroplastik Polipropilena (PP) Terhadap Pertumbuhan 2 Varietas Jagung Lokal Madura - Marchel Putra Garfansa; Agus Hadiyanto; Yenni Arista Cipta Ekalaturrahmah; Iswahyudi Iswahyudi (Politeknik Negeri Lampung., 2026)
This study aimed to compare the growth responses of two local Madurese maize varieties, Talangu and Elos, grown in media contaminated with polypropylene (PP) microplastics, and to identify the variety that showed better adaptive capacity during the early growth stage. The experiment was conducted using a 2 × 2 factorial completely randomized design with three replications. The tested factors consisted of maize variety, namely Talangu and Elos, and growth media condition, namely without PP contamination and with PP contamination. Observations were carried out at 5, 10, and 15 days after sowing on plant height, number of leaves, root length, and plant fresh weight. The results showed that polypropylene microplastic contamination affected the growth responses of both varieties, although the magnitude of the effect varied depending on the observed parameter. In general, the Talangu variety exhibited better growth performance in plant height, root length, shoot fresh weight, and root fresh weight, whereas the Elos variety was relatively better at maintaining leaf number under contaminated conditions. These findings indicate that plant responses to polypropylene contamination are parameter-specific and influenced by varietal differences. Based on the overall early growth responses, the Talangu variety can be considered more tolerant to polypropylene microplastic contamination than the Elos variety.